2002
DOI: 10.1590/s0101-81752002000200002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da alteração ambiental sobre comunidades de Odonata em riachos de Mata Atlântica de Minas Gerais, Brasil

Abstract: ABSTRACT. Effects of environmental degradation on Odonata community of Atlantic Forest streams from Minas Gerais, Brazil. The effect of riparian deforestation and stream impoundments on an odonate community was studied in areas of surviving Atlantic forest in Viçosa and in Rio Doce State Park (PERD), Marliéria, Minas Gerais, Brazil. During 1997 16 species of Libellulidae, 4 Coenagrionidae, 2 Gomphidae, 2 Calopterygidae, 1 Megapodagrionidae, 1 Aeshnidae and 3 Protoneuridae were collected. In Viçosa, the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
0
14

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 22 publications
1
36
0
14
Order By: Relevance
“…Essas alterações diminuem a riqueza local porque homogeneizam os ambientes, diminuindo a disponibilidade de recursos e, criam ilhas de habitats que têm sua recolonização dependente da distância de outros habitats mais adequados (O'CONNOR 1991, ZWICK 1992, WARD 1998. Entretanto, a complexidade de ambientes pode tamponar o efeito da perturbação e os novos ambientes, criados pela ação de agentes perturbadores parecem ser favoráveis a muitas espécies de Odonata (SAMWAYS & STEYTLER 1996, STEWART & SAMWAYS 1998, FERREIRA-PERUQUETTI & DE MARCO JR. 2002.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Essas alterações diminuem a riqueza local porque homogeneizam os ambientes, diminuindo a disponibilidade de recursos e, criam ilhas de habitats que têm sua recolonização dependente da distância de outros habitats mais adequados (O'CONNOR 1991, ZWICK 1992, WARD 1998. Entretanto, a complexidade de ambientes pode tamponar o efeito da perturbação e os novos ambientes, criados pela ação de agentes perturbadores parecem ser favoráveis a muitas espécies de Odonata (SAMWAYS & STEYTLER 1996, STEWART & SAMWAYS 1998, FERREIRA-PERUQUETTI & DE MARCO JR. 2002.…”
Section: Discussionunclassified
“…Para a amostragem das espécies, seguiu-se o método descrito em FERREIRA-PERUQUETTI & DE MARCO JR. (2002). Houve somente modificação da rede utilizada para coleta das larvas (neste trabalho, rede manual tipo "D" com malha de 500 µm).…”
Section: Amostragemunclassified
See 1 more Smart Citation
“…The general dark pattern of thorax in H. consors could be well adapt to leave in shaded areas increasing its absorbing abilities (Hilfert-Ruppell 1998). These morphological and behavioral characteristics suggest this species as associated to forested streams, and probably a good biological indicator of pristine habitats as other species of this genera (Ferreira-Peruquetti & De Marco 2002).…”
Section: Discussionmentioning
confidence: 71%
“…Specifically for the suborder Anisoptera, studies have shown that richness is higher in environments with lower vegetation cover (Carvalho et al, 2013;Juen et al, 2014) and their larvae exhibit considerable resistance to disturbed habitats (Kalkman et al, 2008). Thus, environmental changes as removal of riparian forest can positively affect most species of Anisoptera since the majority is generalist and adapted to sites with higher solar incidence (Ferreira-Peruquetti & De Marco, 2002;Remsburg & Turner, 2009). The Brazilian odonatofauna is still poorly known and most studies address the south and southeast regions (De Marco & Vianna, 2005).…”
mentioning
confidence: 99%